Charge Dynamics in A Donor–Acceptor Covalent Organic Framework with Periodically Ordered Bicontinuous Heterojunctions1. Issue 7 (16th January 2013) - Jin, Shangbin; Ding, Xuesong; Feng, Xiao; Supur, Mustafa; Furukawa, Ko; Takahashi, Seiya; Addicoat, Matthew; El‐Khouly, Mohamed E.; Nakamura, Toshikazu; Irle, Stephan; Fukuzumi, Shunichi; Nagai, Atsushi; et al.
<x xml:space="preserve">Abstract</x> Light works: Mechanistic insights into the photochemical events and charge dynamics of a donor–acceptor covalent organic framework were given by time‐resolved transient absorption spectroscopy and time‐resolved electron spin resonance spectroscopy (see picture). The organic framework triggers ultrafast electron transfer and enables long‐distance charge delocalization and exceptional long‐term charge separation.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>